Studies on a Subcellular System for Vitamin K- Dependent Carboxylation - Wallin, R; Prydz, H (Thrombosis and Haemostasis, 1979)
The subcellular localization of acarboxyprothrombin and the vitamin K-dependent carboxylation system has been studied using livers from vitamin K-deficient rats and found to be mainly in the membranes of the rough microsomal fraction. Bovine acarboxyprothrombin or fragment 1 thereof were inactive as substrates in the rat carboxylating sytem.